2020
DOI: 10.1109/access.2020.2991329
|View full text |Cite
|
Sign up to set email alerts
|

The V2G Process With the Predictive Model

Abstract: The paper proposes using a predictive model to optimize the use of electricity in the V2G (vehicle to grid) service. The novelty of the mechanism as a kind of model predictive control (MPC) is that it seeks an effective way of managing electric energy in an Electric Vehicle (EV). Additionally, it proposes a new method of predicting the electricity consumption which allows the battery of an electric vehicle to reconcile two sides: both the system's and the user's demand will be met at the same time. The model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…As investigated and demonstrated in several published studies, as in [17], [18], [19], [19], [20], [21], [22], and [23], this option of bidirectional power interface has an extremely vital impact, permitting, for example, to control the EV to overcome issues of efficiency and power quality in the power grid. In this standpoint, with the consent of the EV driver (e.g., guaranteeing advantageous tariffs for programs of power management sustained by the G2V/V2G modes, and knowing that the EV battery can be degraded when subjected to additional charge/discharge cycles), the EV can be controlled by an algorithm of power management of the smart home or smart grid, which outlines the programming modes for charging (G2V) and discharging (V2G) processes [24].…”
Section: Ev In Smart Homes and Smart Grids: Overview Of Operation Modesmentioning
confidence: 99%
“…As investigated and demonstrated in several published studies, as in [17], [18], [19], [19], [20], [21], [22], and [23], this option of bidirectional power interface has an extremely vital impact, permitting, for example, to control the EV to overcome issues of efficiency and power quality in the power grid. In this standpoint, with the consent of the EV driver (e.g., guaranteeing advantageous tariffs for programs of power management sustained by the G2V/V2G modes, and knowing that the EV battery can be degraded when subjected to additional charge/discharge cycles), the EV can be controlled by an algorithm of power management of the smart home or smart grid, which outlines the programming modes for charging (G2V) and discharging (V2G) processes [24].…”
Section: Ev In Smart Homes and Smart Grids: Overview Of Operation Modesmentioning
confidence: 99%
“…Electric vehicles (EVs) have become popular due to several environmental and economical advantages compared to fossil fuel cars such as reducing pollution, greenhouse gas emission, and operation cost [1]. In modern transportation systems, EVs are the preferred choice due to their energy and environmental sustainability, although they often fail to find proper charging stations due to the limited infrastructure of Smart Grid (SG) and unbalance demand of charging.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the efficient management of the EVs charging/discharging to reduce cost has become challenging due to random EV's arrival and departure times, randomness of the EVs' utility, and dynamic price of energy. In V2G, EVs can be used for excess energy storage from the SG to balance energy demand, smooth demand peak, and eliminate distribution losses [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [ 18 ] propose using the BLDC motor thermal model to optimize the trajectory of the industrial robot movements, taking into account thermal constraints. Moreover, based on the research conducted by the authors in [ 19 ], it can be concluded that thermal modeling of a traction motor with permanent magnets will have a significant impact on the optimization of V2G (vehicle to grid) systems, because the amount of energy consumed by an electric vehicle is dependent on thermal losses of its motor.…”
Section: Introductionmentioning
confidence: 99%